1991
DOI: 10.1007/bf01887332
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cholecystostomy in critically Ill patients

Abstract: Sixteen critically ill patients underwent percutaneous cholecystostomy because of suspected acute cholecystitis. The procedure was technically successful, although 11 of 16 patients died subsequently because of various complications of their underlying primary disorders. We reviewed this series to reassess the value of percutaneous cholecystostomy. Four of 11 patients with definite acute cholecystitis (group 1) were cured by this technique, but three required surgery because of gallbladder wall necrosis. Two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
15
2
Order By: Relevance
“…Similarly, intramural wall lucencies, defined as irregular discontinuous lucent and echogenic bands in the gallbladder wall [1], were not seen in either of the two patients who developed acalculous cholecystitis, but were seen in 15% of patients who did not develop acalculous cholecystitis. Localized pericholecystic fluid (defined as fluid around the gallbladder alone, not associated with ascites) has been reported to show some specificity for acute cholecystitis [3,8]; however, in our study, this fluid was found in 19% of patients, none of whom developed acalculous cholecystitis.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Similarly, intramural wall lucencies, defined as irregular discontinuous lucent and echogenic bands in the gallbladder wall [1], were not seen in either of the two patients who developed acalculous cholecystitis, but were seen in 15% of patients who did not develop acalculous cholecystitis. Localized pericholecystic fluid (defined as fluid around the gallbladder alone, not associated with ascites) has been reported to show some specificity for acute cholecystitis [3,8]; however, in our study, this fluid was found in 19% of patients, none of whom developed acalculous cholecystitis.…”
Section: Discussioncontrasting
confidence: 78%
“…Multiple static images were obtained in the sagittal and transverse planes of the gallbladder, and wall thickness was measured from transverse images relative to the long axis of the gallbladder. The images were examined together by two radiologists for sonographic features consistent with acalculous cholecystitis features that have been described: gallbladder wall thickening, gallbladder distention, intramural gallbladder wall lucencies (striated gallbladder wall), pericholecystic fluid, gallbladder sludge, and the presence of a sonographic Murphy's sign [1][2][3][4][5][6][7][8][9]. Gallbladder wall thickening was defined as a transverse wall measurement adjacent to the liver and perpendicular to the sonography beam of greater than 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24][25][26] In the present study the mortality rate in PC group was 13%, which was higher than in the LC group but not statistically significant. [21][22][23][24][25][26] In the present study the mortality rate in PC group was 13%, which was higher than in the LC group but not statistically significant.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have reported response rates of 63-93% [24,25] and 80% [25], respectively. AAC has been associated with a high incidence of gallbladder wall gangrene [9,14,25,26], in which a non-surgical treatment could be insufficient and an explanation of a lower response rate. The finding of pericholecystic fluid on Us could be an indicator of a gangrenous gallbladder [25] and has been found to be a negative predictor for response by some authors [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…AAC has been associated with a high incidence of gallbladder wall gangrene [9,14,25,26], in which a non-surgical treatment could be insufficient and an explanation of a lower response rate. The finding of pericholecystic fluid on Us could be an indicator of a gangrenous gallbladder [25] and has been found to be a negative predictor for response by some authors [25,26]. Lo et al [25] suggested that surgical intervention should be 215 this specific case, the gallbladder was punctured transperitoneally, because of individual anatomy of the liver.…”
Section: Discussionmentioning
confidence: 99%